Professional negligence of doctors / Nor Aini Mohd Arif - Mohd Arif, Nor Aini (Faculty of Law, 1985)
There is no doubt that professional negligence is a matter of increasing concern to professionals and the public alike. It is unknown how'often patients sue their doctors for negligence.These actions are likely to increase with the growing public reliance on health care sevices. There is no statutory law for professional negligence and therefore the negligence of doctors is an area of law whichis based on judicial decisions. It requires a detailed study of various cases to see how they have developed the law. One important legal consequence-421‘ this has been the development of the law on medical negligence, particularly in the area of the standard of care owed by doctors to their Ipattients.In this context. it is proposes to examine the obligations and liability of medical men in the various aspects of their work,and. since the study is based on judicial decisions and not statutory law, the discussions will therefore be based primarily on cases.